PENGARUH AKUNTANSI MANAJEMEN LINGKUNGAN TERHADAP KINERJA MASA DEPAN MELALUI INOVASI (Studi Empiris pada Perusahaan Manufaktur di Indonesia Tahun 2017 - 2021) - Nugafira, Fathiyya Reihana Aqilla; Prasetyo, Andrian Budi (Diponegoro Journal of Accounting, 2024)
This study aims to evaluate the effect of environmental management accounting (EMA) on future performance, with innovation as a mediating variable.  Future performance is measured through the following year's Return on Assets (ROAt+1), serving as the dependent variable. EMA is measured through the difference between the previous and current year's production costs divided by total sales, which is the independent variable. Meanwhile, innovation, measured by R&D costs to total assets, acts as a mediating variable. The data for this study come from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2021 period, with 110 samples selected through purposive sampling method for five consecutive years. This study uses multiple linear regression analysis to test the proposed hypothesis. Through multiple linear regression models, the relationship between environmental management accounting, future performance, and innovation can be identified. The results of this study show that environmental management accounting has no effect on innovation and future performance, as well as innovation does not mediate the relationship between environmental management accounting and future performance. However, there is evidence that innovation has a significant effect on future performance.